Uterine Smooth Muscle Tumors of Unknown Malignant Potential (STUMP): A Dilemma for Gynecologists and Pathologists - Derman Başaran; Nejat Özgül; İlker Selçuk; Gökhan Boyraz; İbrahim Kulaç; Alp Usubütün; Kunter Yüce; Sinan Beksaç (Gynecology Obstetrics & Reproductive Medicine)
Uterine smooth muscle tumors of uncertain malignant potential (STUMP) belong to a subcategory of uterine smooth muscle tumors. The clinical behavior of these tumors is also not clarified. It is hard to state which histological features of STUMPs might represent high recurrence rates. The follow up period also has not been mentioned. For clinicians, STUMPs are difficult tumors to manage since they clinically present as ordinary fibroids. For pathologists, diagnosis of these tumors could be difficult because these tumors are rare and a certain level of expertise in gynecological pathology is required to make a correct diagnosis. Here we report a patient with STUMP that subsequently recurred as a leiomyosarcoma, aiming to remind the disease and its recurrence risk even if followed strictly.